Petrogenesis of the Early Silurian Renda appinite suite in the southeastern Qilian Orogen, NW China: Implications for the evolution of a Proto-Tethys magmatic arc. Issue 19 (28th October 2022) - Li, Xi-Yao; Li, Sanzhong; Yu, Shengyao; Liu, Yongjiang; Liu, Yiming; Guo, Xiaoyu; Zhao, Hao; Zhao, Shujuan
ABSTRACT: Early Paleozoic subduction beneath peri-Gondwana microcontinents formed a major Proto-Tethys magmatic arc system. Appinite suite rocks constitute important components within that magmatic arc. Herein, we report hornblende 40 Ar/ 39 Ar and zircon U–Pb geochronology data, zircon Hf isotope, mineral chemistry, whole-rock geochemistry, and Sr–Nd–Pb isotope data for the rocks of hornblende gabbro-diorite-quartz diorite-quartz monzodiorite from the Renda appinite suite and adjacent granite porphyry in the southeastern Qilian Orogen. Hornblende 40 Ar/ 39 Ar and zircon U–Pb isotopic data constrain ages of the intrusions of the Renda appinite suite to 439–435 Ma. Rocks in this suite represent the calc-alkalic to alkali-calcic series, and they are enriched in large-ion lithophile elements and depleted in high-field-strength elements. The hornblende gabbros exhibit moderate initial 87 Sr/ 86 Sr ratios (0.7046–0.7055) and higher whole-rock εNd (t) (–1.3 to +1.7) and zircon εHf (t) (+7.2 to +11.2) values relative to the other rocks of the suite (0.7047–0.7064, – 7.7 to – 1.1, and – 6.6 to +6.8, respectively) as well as Pb isotopic features similar to EM2 lithospheric mantle. These geochemical characteristics suggest that the Renda appinite suite originates from partial melting of an enriched lithospheric mantle, with subsequent fractional crystallization and hybridization with crustal components. The granite porphyry formed by partial melting of the crust coeval with the emplacement of juvenile magma. This study suggests emplacement occurred during a short-lived collision with slab failure (breakoff) after latest stage (cessation) of Proto-Tethys oceanic subduction along the northern side of the southeastern Qilian Orogen. The heat supplied by the asthenospheric upwelling through a gap in the subducted slab induced melting in lithospheric mantle and deep crust producing Renda appinite suite rocks and granite porphyry.